Comparison of Platelet-Rich Plasma-Impregnated Suture Material with Low and High Platelet Concentration to Improve Colonic Anastomotic Wound Healing in Rats - Mehmet Akif Aydin; Eray Metin Guler; Ahu Senem Demiroz; Muhammet Fatih Aydin; Gulcan Saglam (Gastroenterology Research and Practice)
Objective. This study was designed to investigate the impact of using suture material impregnated with platelet-rich plasma (PRP) in different platelet concentrations on colonic anastomotic wound healing in rats. Methods. A total of 24 Sprague Dawley female rats were separated into 3 groups (n=8 for each) including the control group (CON; standard vicryl suture repair), the low platelet concentrate PRP group (L-PRP; suture material impregnated with PRP containing average 2.7-fold (range, 2.0 to 3.1) higher amount of platelets vs. control), and the high platelet concentrate PRP group (H-PRP; suture material impregnated with PRP containing average 5.1-fold (range, 4.8 to 5.4) higher amount of platelets vs. control). Rats were sacrificed on the postoperative 7th day for analysis of colonic anastomosis region including macroscopic observation, measurement of anastomotic bursting pressure (ABP), and the hydroxyproline levels and histopathological findings in colon tissue samples. Results. Total injury scores were significantly lower in the L-PRP and H-PRP groups than those in the control group (median (range) 13.00 (7.00) and 11.50 (6.00) vs. 15.50 (4.00), p<0.05 and p<0.01, respectively). ABP values (180.00 (49.00) vs. 124.00 (62.00) and 121.00 (57.00) mmHg, p<0.001 for each) and tissue hydroxyproline levels (0.56 (0.37) vs. 0.25 (0.17) and 0.39 (0.10) μg/mg tissue, p<0.001 and p<0.05, respectively) were significantly higher in the L-PRP group as compared with those in the control and H-PRP groups. Conclusion. In conclusion, our findings revealed PRP application to colonic anastomosis sutures to promote the anastomotic healing process. The platelet concentration of PRP seems to have a significant impact on the outcome with superior efficacy of L-PRP over H-PRP in terms of bursting pressures and collagen concentration at the anastomotic site.